A comparative life cycle assessment of drip and flood irrigation of in-shell pecan production in the Mesilla Valley, New Mexico, United States - Raji Lukkoor; Colleen C. Naughton; Sara M. Torres; Richard Heerema; Rolando A. Flores Galarza; Joshua H. Viers; Alexander G. Fernald (Agricultural Water Management)
Quantifying the water use and environmental impacts of irrigated crops in arid regions is essential for sustainable agriculture. The arid southwestern state of New Mexico in the United States (US) is a major producer of pecans, a water-intensive crop. Climate change-induced surface water scarcity has increased reliance on pumped groundwater, resulting in higher emissions and causing aquifer depletion. This study uses a life cycle assessment (LCA) to quantify and compare the water use and environmental impacts of one kilogram of in-shell pecan production using drip and flood irrigation, making this the first LCA of pecan production. The cradle-to-farm gate system boundary includes the life cycle stages of pruning, irrigation, production, and harvest. Primary data sources include interviews with Mesilla Valley pecan producers, New Mexico State University extension publications and specialists, and state and County agriculture reports. Data analysis and modeling were conducted using the LCA software SimaPro 9.6.0.1. Four impact categories were assessed, including global warming potential, smog, ecotoxicity, and fossil fuel depletion. The production life cycle stage had the highest emissions (59–78 % across the four impact categories), driven by fertilizer production. Groundwater pumping accounted for 12–34 % of emissions in the four impact categories. Flood irrigation with groundwater reduced emissions by 63–87 % per kilogram of yield compared to drip irrigation with groundwater. A twofold system combining flood irrigation with surface water and drip irrigation with groundwater is recommended to balance aquifer recharge and emissions reductions. These findings can guide sustainable practices for pecans and other orchard crops in arid regions.